Parenteral Vaccination With a Tuberculosis Subunit Vaccine in Presence of Retinoic Acid Provides Early but Transient Protection to M. Tuberculosis Infection - Riccomi, Antonella; Piccaro, Giovanni; Christensen, Dennis; Palma, Carla; Andersen, Peter; Vendetti, Silvia (Frontiers in Immunology, 2019)
Most microbes invading through mucosal surfaces cause disease and therefore strategies to induce mucosal immune responses are strongly needed. Vitamin A metabolites, such as retinoic acid (RA), play crucial roles in programming T and B cells to home to mucosal compartments, therefore we evaluated the capacity of RA to elicit mucosal immune responses against tuberculosis (TB) after parenteral vaccination. We found that mice immunized through subcutaneous injections with the TB subunit vaccine (CAF01+H56) in presence of RA show enhanced mucosal H56-specific IgA responses and enhanced Ag-specific CD4+ T lymphocytes homing to the lung as compared with control mice. Immunization with CAF01+H56 in presence of RA resulted in lower bacterial loads in the lungs of mice 14 days after challenge with virulent Mycobacterium tuberculosis (Mtb) as compared to mice immunized in the absence of RA or vaccinated with BCG. Higher amounts of IFNγ and IL-17 pro-inflammatory cytokine were found in lung homogenates of mice immunized with CAF01+H56 and RA 24 hours after Mtb infection. However, 6 weeks after infection the protection was comparable in vaccinated mice with or without RA even though treatment with RA during immunization is able to better contain the inflammatory response by the host. Furthermore, at later stage of the infection a higher percentage of Mtb specific CD4+PD1+ T lymphocytes were found in the lungs of mice immunized with CAF01+H56 and RA. These data show that an enhanced mucosal immune response is generated during parenteral vaccination in presence of RA. Furthermore RA treatment contained the bacterial growth at an early stage of the infection and limited the inflammatory response in the lung at later time points.